The Effect of an Industrial Area on The Socio – Economic Invirontment in Bitung City - Langingi, Julius (JBE (Journal of Business and Economics); Volume 5 No.1, 2006 JBE UNKLAB, 2006)
The primary objective of this study is to investigate the impact of an industrial parj towards their socio-economics in Bitung City. The largets manufacturing plants in number of twenty-four (24) among the forty-four (44) manufacturing plants/industries over the city are located in the sixty sub-districts of Bitung City with a total of the city population of 162,994 people. The socio-ecinomic factors are believed to have profound effects on the indrustries revenue, sustainability and growth, which in turn, affect economic growth of the region. Using the sample of seventy-two (72) respondents from the middle district ofthe city, the research warted to test the null hypothesis, that industrial park in Bitung does not have a significant effect on the socio-economic environment of the city. The descriptive research method applying Likert scale with a statistical z-test is used to answer the basic problem of the study. Statistical tests show that the null hypothesis should be rejectedin favor of the alternative hypotesis. The study conclusively proves, at the 95% level of significance, that citizenry of Bitung perceived that the industrial park growing around thir neighborhood has a positive affect on the socio-economic welfare of the region.